KETERLIBATAN APARATUR SIPIL NEGARA DALAM PEMILIHAN KEPALA DAERAH SERENTAK KABUPATEN POLEWALI MANDAR TAHUN 2018 - Munawir Ariffin; Abdul Latief; Muhammad Assaibin (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2019)
This study departs from the involvement of the State Civil Apparatus (ASN) in the Regional Head Election (Pilkada) Simultaneous Polewali Mandar Regency in 2018. Based on data from the Election Supervisory Board (Bawaslu) Polewali Mandar Regency, there are 17 cases of ASN involvement of Polewali Mandar Regency reported by the public to Bawaslu Regency of Polewali Mandar. The neutrality issue of the State Civil Apparatus (ASN) controversy So that the tendency is still for the ASN to carry out practical political activities both campaigning and supporting supporting the pair of candidates in the regional election equipment. Substantially, the focus of Law Number 5 of 2014 concerning State Civil Apparatus it only makes civil servants the object of neutrality, apart from the dynamics of practical political activities that are full of intervention. The active role of the bureaucratic leadership in encouraging the implementation of ASN neutrality in the elections is still minimal, causing neutrality in the elections not only because of the practical political interests of individual ASNs, but also the weak internal policy of regional leaders to disseminate and ban ASN in the elections, particularly also in the Simultaneous Regional Election of Polewali District Mandar in 2018.